CONTRIBUTIONS OF THE CERAMIC ANALYSIS ON THE USE OF SPACE IN THE PASTORALIST POST PICHANAL 4 PASTORAL OUTPOST (SIERRA DEL CAJÓN, PROVINCE OF CATAMARCA) - Rampa, Daniel Alfredo (Instituto Nacional de Antropología y Pensamiento Latinoamericano, 2024)
Pichanal 4 is a pastoral site located in the Sierra del Cajón (Province of Catamarca) at 2,700 m above sea level. It is made up of 12 structures, with enclosure 1 (isolated from the others) at the lowest part and enclosure 12 at the highest. It has been postulated that nine large, irregular enclosures may have been corrals, while the smaller spaces may have housed the shepherd on duty or stored foodstuffs and tools of the shepherd's trade. This paper expands the ceramic sample analysed and evaluates the distribution of ceramic styles and frequencies among the different enclosures of the post using statistical methods, a methodology not previously employed in the analysis of pottery assemblages from the site.